Respuesta :

Answer:

[tex](g\circ f)(-1)=36[/tex]

Step-by-step explanation:

We are given the two functions:

[tex]f(x)=-x+5\text{ and } g(x)=x^2[/tex]

And we want to find:

[tex](g\circ f)(-1)[/tex]

This is equivalent to:

[tex]=g(f(-1))[/tex]

So, evaluating f(-1) first, we acquire:

[tex]f(-1)=-(-1)+5=6[/tex]

Then by substitution:

[tex]=g(6)[/tex]

So:

[tex]=(6)^2=36[/tex]

Therefore:

[tex](g\circ f)(-1)=36[/tex]

Your answer is indeed correct.

Answer:

please refer to the above attachment.

36 is the right answer.

Ver imagen manissaha129

Otras preguntas